THE Effect Of Visual Media Education On The Level Of Knowledge Of The Elderly About The Prevention Of Hypertension - Adi Nurapandi; Irpan Ali Rahman; Endrian MJW; Annisa Miranda; Nabil Ridla Firdaus; Gita Yulianasari; Heny Marliany; Sugiarto (HealthCare Nursing Journal, 2025)
Hypertension is high blood pressure whose systolic is more than 140 mmHg and diastolic is more than 90 mmHg. Hypertension in the elderly is mostly isolated systolic blood pressure (HST), with increased systolic blood pressure leading to an increased risk of myocardial infarction and stroke even when the diastolic is in the normal range. Prevention efforts are made by providing education about the prevention of hypertension to the elderly who have never experienced hypertension. This study aims to determine the effect of education through Visual media on the level of knowledge of the elderly about the prevention of hypertension. quantitative research using quasi experiment design, the design used is one group pre-test post-test design. Number of participants involved in this study was 55 participants and sampling in this study with Probability Sampling technique using multi stage random sampling method. Participants involved in this Reasearch were those who met the inclusion and exclusion criteria, namely the elderly who did not have a history of hypertension in the Selasari. This research was conducted in February - April 2024. The intervention was given after the participants filled in the queationer (pre test) and the measurement was carried out after the intervention was given in the form of filling out the questioner (post test). The measurement results were recorded in the observation sheet to be analyzed using SPSS Version 26 software with statistical tests. Data on participant characteristics are displayed in frequencies and percentages while the effect of the intervention is expressed in P-Value. The study states that there is an effect of education through visual media on the level of knowledge of the elderly about preventing hypertension with a significance value on the results of the Paired T-Test test obtained ρ-value (0.000) < α (0.05). Education through Visual Media affects the level of knowledge of the elderly about the prevention of hypertension.